Indicadores de vulnerabilidade, risco socioambiental e educação ambiental para prevenção e mitigação de desastre natural na bacia hidrográfica do Tucunduba, Belém-PA - SILVA JÚNIOR, Antônio Rodrigues da (Universidade Federal do Pará, 2018)
The present research aimed to analyze the hidroclimatics phenomena that cause natural disasters, flood-related, and flooding in the catchment area of the Tucunduba-BHT, specifically in the neighborhood Montese, Belém-PA and its interfaces with the physical geomorphological factors of ground and with human actions, which leverage the magnitude of these disasters. This research presents still environmental education as a management tool, not only from its reductionist vision, restricted to human action of depositing waste in inappropriate places, but most of all, from a systemic, interdisciplinary and critic discussion that problematize the complex relations involving environmental issues in its multiple aspects, in addition to the bureaucratic formalism, and build new rational cultures that make it possible to develop actions of transformations and emancipations that actually contribute to the social well-being. For that, were performed several field research that sought to identify the vulnerability and designing environmental education of the population resident in the neighborhood Montese, to draw the profile of the resident of that neighborhood, to identify points of flood and flooding and the actions of the organs legally responsible for the management of risks and natural disasters. Therefore, it was concluded that the cases of flooding in Montese neighborhood will continue to occur, given the physical characteristics of the land and the high rainfall in the region, but, above all, by the absence or ineffectiveness of integrated territorial planning focused on the specificity of the local population public policy, the need for continuous and permanent programs and actions of environmental education in the community, with the purpose of providing environmental rationality and/or awareness that transforms the human being and your space lived, as well as by the precariousness of basic constitutional rights of the citizen.